2009
DOI: 10.1186/1471-2105-10-441
|View full text |Cite
|
Sign up to set email alerts
|

The Medicago truncatula gene expression atlas web server

Abstract: BackgroundLegumes (Leguminosae or Fabaceae) play a major role in agriculture. Transcriptomics studies in the model legume species, Medicago truncatula, are instrumental in helping to formulate hypotheses about the role of legume genes. With the rapid growth of publically available Affymetrix GeneChip Medicago Genome Array GeneChip data from a great range of tissues, cell types, growth conditions, and stress treatments, the legume research community desires an effective bioinformatics system to aid efforts to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
164
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(170 citation statements)
references
References 33 publications
1
164
0
5
Order By: Relevance
“…We examined a putative cell wall peroxidase, cwPRX2 (GenBank accession no. AES66966.1; Medtr2g084000), with high expression levels in roots according to the M. truncatula Gene Expression Atlas (Benedito et al, 2008;He et al, 2009) and with 82% amino acid identity to the cell wall-localized PsPOX11 peroxidase from Pisum sativum (Kawahara, 2006). We found that the expression of cwPRX2 was signficantly up-regulated in latd mutant roots and up-regulated by ABA only in latd mutants (Fig.…”
Section: Decreasing Ros Levels Can Increase Cell Elongation In Latd Rmentioning
confidence: 70%
“…We examined a putative cell wall peroxidase, cwPRX2 (GenBank accession no. AES66966.1; Medtr2g084000), with high expression levels in roots according to the M. truncatula Gene Expression Atlas (Benedito et al, 2008;He et al, 2009) and with 82% amino acid identity to the cell wall-localized PsPOX11 peroxidase from Pisum sativum (Kawahara, 2006). We found that the expression of cwPRX2 was signficantly up-regulated in latd mutant roots and up-regulated by ABA only in latd mutants (Fig.…”
Section: Decreasing Ros Levels Can Increase Cell Elongation In Latd Rmentioning
confidence: 70%
“…3). The early MeJA response of MKB1 was confirmed in the M. truncatula Gene Expression Atlas (MtGEA; http://bioinfo.noble.org/geneatlas/) 15 (Fig. 1b).…”
mentioning
confidence: 78%
“…These transcriptional regulators were projected onto MatNet ( Figure 2C, red symbols). Using data from the Medicago Gene Expression Atlas MtGEA (He et al, 2009) and our own transcriptomic data sets (Verdier et al, 2013), we also identified probes preferentially expressed in seeds in comparison to other tissues. Out of the 2912 nodes present in MatNet, 198 had transcription levels >100-fold higher in seed versus non-seed tissues (blue symbols).…”
Section: Generation and Characterization Of Matnet: A Robust Coexpresmentioning
confidence: 99%